Maslahah Mursalah: Pendekatan Alternatif Perbankan Syariah dalam Menyelesaikan Krisis Kemanusiaan Rohingya di Aceh: Maslahah Mursalah: An Alternative Approach for Islamic Banks to Addressing the Rohingya Refugee Crisis in Aceh, Indonesia - Munawar Jailani; Ousmane Salifou Abdou; Danial; Dicky Armanda; Andi Mardika; Mohamad Zaim Isamail (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The humanitarian crisis for Rohingya refugees in Aceh has reached its worst levels. Various institutions have attempted to address this crisis, including Islamic banks; however, due to regulations and policies, these institutions are limited in their ability to provide further assistance. This article explores the concept of maslahah mursalah as an alternative approach to policymaking that Islamic banks can use to help alleviate the humanitarian crisis affecting Rohingya refugees in Aceh. This research uses a qualitative descriptive approach. Primary data sources include books discussing the interests of two reformers, while secondary data was collected from newspapers, books, and articles examining Islamic banking in Aceh and issues facing the Rohingya community. The findings of this study indicate that: (1) the principle of maslahah is an Islamic principle that can serve as a basis for Islamic banks to develop policies aimed at assisting the Rohingya in Aceh, as this urgent need is not currently being addressed by these banking institutions. (2) The humanitarian crisis of Rohingya refugees in Aceh is considered a necessary need, according to the definitions established by scholars such as Al-Ghazali, Ibn Ashour, and Al-Shatibi. (3) We believe that the humanitarian crisis of Rohingya refugees in Aceh can be addressed by Islamic banks, which include 28 banks — seven Sharia commercial banks, six Sharia business units, and 15 people's credit banks — from corporate social responsibility funds to help 1,104 Rohingya refugees who are sheltered in four locations across Aceh: Bedi, Sabang, North Aceh, and East Aceh.